A Employee Readiness and Implementation of Risk Management in the Work Rule Changes / Standard Operation Procedure and Its Effect on Performance - Renwarin, Joseph M J (International Journal of Innovation Research in Education, Technology and Management, 2024)
The purpose of this research is to understand the effect of employee readiness and Risk Management Implementation at pharmacy company Group in facing SOP/work rules changes and its effect to the performances. This research is a quantitative research that using survey method conducted to the Personnel that implementing Risk Management at entities in Pharma Company Group. Sample taken as a Purposive - Non probability Sampling. Research result shows that there is no significant influence between employees readiness with SOP/work rules changes. Risk Management Implementation will give a significant affect to SOP/Work rules changes. Employee readiness and risk management implementation simultaneously give a significant affect to SOP/ Work rules changes. SOP/ Work rules changes will give a significant affect to performances.